Water excess and its effect on cassava growth and yield - Ferigolo Alves, Alexandre; de Oliveira de Freitas, Charles Patrick; Junior Zanon, Alencar; Streck, Nereu Augusto; de Souza Cardoso, Paula; de Andrade Tardetti, Felipe (Revista Ceres, 2024)
Flooding periods directly interfere with the availability of oxygen in the soil, affecting the aerobic processes of the plants. In this study, we aimed to: (i) characterize the effects of water excess soil on cassava growth; (ii) identify management practices that reduce the impact of water excess on cassava yield; and (iii) to know the crop potential yield for the study region in order to quantify the yield loss caused by water excess. The effects of water excess were evaluated through experiments in pots and in the field. The physiological and morphological response of cassava plants under water excess in a controllable environment indicated greater damage to cassava after exposure of 96 and 120 hours of water excess. Every 24 hours of water excess, about 20% of the plants did not emerge and, after 96 hours of excess, the emergence was null. The use of raised seedbeds was a management practice that ensured 62.6% of plant establishment, allowing cassava yields of up to 16.9 Mg ha-1. The potential yield to Santa Maria in the 2018/2019 crop year was 43.9 Mg ha-1 of cassava roots. The yield gap caused by water excess was up to 4.1 Mg ha-1.